Elucidation of the biosynthesis of carnosic acid and its reconstitution in yeast - Ulschan Scheler (Nature Portfolio, 2016)
Diterpenes are plant products with high antioxidant properties and potential application as food additives and therapeutics. Here, the authors describe the complete biosynthetic pathway of carnosic acid and reconstruct it in yeast, opening the way to metabolic engineering of phenolic diterpenes.